Kinematics Analysis and Simulation of Rehabilitation Wearable Upper Limb Exoskeleton based on Adams - Jiqun Yu; Ning Liu; Lü Qiongying (Jixie chuandong)
To assist physically disabled people with impaired upper limb function， a new exoskeleton robot is developed， which named motion assistive robotic-exoskeleton for superior extremity to ease daily upper limb movements and to provide effective rehabilitation therapy to the superior extremity. Firstly， the entire wearable robot is designed and modeled in ergonomics. The D-H coordinates are established by the exoskeleton upper limb kinematics model， and use Lagrange method to analyze its dynamics， and the theoretical driving torque of each joint is solved. The dynamics analysis software Adams is used to simulate the robot. By planning the end and active trajectory and speed settings， the changes of torque， speed and acceleration of each joint are obtained. The correctness of the dynamics model is verified in reverse， and the foundation for further optimization of robot is laid.